# CBSEtips.in

## Thursday, 25 February 2021

### CBSE Class 7 Maths - MCQ and Online Tests - Unit 12 - Algebraic Expressions

#### CBSE Class 7 Maths – MCQ and Online Tests – Unit 12 – Algebraic Expressions

Every year CBSE students attend Annual Assessment exams for 6,7,8,9,11th standards. These exams are very competitive to all the students. So our website provides online tests for all the 6,7,8,9,11th standards’ subjects. These tests are also very effective and useful for those who preparing for any competitive exams like Olympiad etc. It can boost their preparation level and confidence level by attempting these chapter wise online tests.

These online tests are based on latest CBSE syllabus. While attempting these, our students can identify their weak lessons and continuously practice those lessons for attaining high marks. It also helps to revise the NCERT textbooks thoroughly

#### CBSE Class 7 Maths – MCQ and Online Tests – Unit 12 – Algebraic Expressions

Question 1.
What is the coefficient of x in the expression ax3 + bx2 + d?
(a) a
(b) b
(c) d
(d) 0

Question 2.
What is the coefficient of x2 in the expression ax + b?
(a) a
(b) b
(c) a + b
(d) 0

Question 3.
What is the coefficient of x in the expression 2x + xy2?
(a) 2 + y2
(b) 2
(c) y2
(d) None of these

Question 4.
What is the coefficient of y2 in the expression 4 – xy2?
(a) 4
(b) x
(c) -x
(d) None of these

Question 5.
How many terms are there in the expression 1.2ab – 2.4b + 3.6a?
(a) 1
(b) 2
(c) 3
(d) 4

Question 6.
How many terms are there in the expression – 2p3 – 3p2 + 4p + 7?
(a) 1
(b) 2
(c) 3
(d) 4

Question 7.
What is the coefficient of x in the expression 4x + 3y?
(a) 1
(b) 2
(c) 3
(d) 4

Question 8.
What is the coefficient of x in the expression 2 – x + y?
(a) 2
(b) 1
(c) -1
(d) None of these

Question 9.
What is the coefficient of x in the expression 1 + x + xz?
(a) z
(b) 1 + z
(c) 1
(d) 1 + x

Question 10.
How many terms are there in the expression 2x2y?
(a) 1
(b) 2
(c) 3
(d) 4

Question 11.
How many terms are there in the expression 2y + 5?
(a) 1
(b) 2
(c) 3
(d) 4

Question 12.
What is the coefficient of y2 in the expression 3y2 + 4x?
(a) 1
(b) 2
(c) 3
(d) 4

Question 13.
What is the coefficient of y2 in the expression 2x2y – 10xy2 + 5y2?
(a) 5 – 10x
(b) 5
(c) -10 x
(d) None of these

Question 14.
What should be added to x2 + y2 to get x2 + y2 + 2 xy?
(a) xy
(b) 2xy
(c) 4xy
(d) -2xy

Hint:
x2 + y2 + 2xy – (x2 + y2) = 2xy

Question 15.
What should be subtracted from x2 + y2 – 2xy to get x2 + y2?
(a) 2xy
(b) -2xy
(c) xy
(d) – xy

Hint:
x2 +y2 – 2xy – (x2 + y2) = -2xy

Question 16.
Which of the following pairs of terms is a pair of like terms?
(a) 1, 10
(b) y, -xy
(c) z2, Z
(d) Z2, 8

Question 17.
Which of the following pairs of terms is a pair of like terms?
(a) 7xy, 14yx
(b) m2p, mp2
(c) 6xz, 12 x2 z2
(d) -13x, -13y

Question 18.
Which of the following pairs of terms is a pair of like terms?
(a) 3x, 2xy
(b) -xy2, – 2xy2
(c) -6x2, 20x2y
(d) 8x2, 7y

Question 19.
Which of the following pairs of terms is a pair of like terms?
(a) 7p, 8q
(b) 10pq, -7qp
(c) 12q2 p2, -5p2
(d) 2405p, 78qp

Question 20.
Which of the following pairs of terms is a pair of unlike terms?
(a) -p2q2, 12q2p2
(b) 41, 100
(c) qp2, 13p2q
(d) -4yx2, -4xy2

Question 21.
Add 2 mn, -4 mn, 8 mn, -6 mn
(a) 0
(b) 2 mn
(c) 8 mn
(d) 10 mn

Hint:
2 + (-4) + 8 + (-6) = 0

Question 22.
Add a + b – 1, b – a + 1, 1 – 26
(a) 1
(b) -1
(c) 2
(d) -2

Hint:
Sum = (1 – 1)a + (1 + 1 – 2)b – 1 + 1 + 1 = 1

Question 23.
(a) x2y
(b) xy2
(c) xy
(d) -x2 y

Hint:
(4 – 3)xy + (-7 +7)xy2 = x2y

Question 24.
Simplify : p + (p – q) + q + (q – p)
(a) p
(b) q
(c) p + q
(d) p – q

Hint:
p + p – q + q + q – p = p + q

Question 25.
Simplify : z2 + 11z2 – 5z – 11z2 + 5z
(a) z2
(b) -z2
(c) 5z
(d) -5z

Hint:
(-1 + 11 – 11)z2 + (5 – 5)z = -z2

Question 26.
Find the value of the expression – x + 2 for x = -2
(a) 1
(b) 2
(c) 3
(d) 4

Hint:
-(-2) + 2 = 2 + 2 = 4

Question 27.
Find the value of the expression 3p + 7 for p = -2
(a) 1
(b) -1
(c) 2
(d) -2

Hint:
3(-2) + 7 = 1

Question 28.
Subtract – xy from xy
(a) xy
(b) 2xy
(c) 3xy
(d) 4xy

Hint:
xy – (-xy) = xy + xy = 2xy

Question 29.
Subtract y2 from – 5y2
(a) -6y2
(b) 6y2
(c) y2
(d) -5y2

Hint:
-5y2 – y2 = -6y2

Question 30.
Find the value of the expression x + 2 for x = -2
(a) 0
(b) 2
(c) -2
(d) 4

Hint:
-2 + 2 = 0

Question 31.
Find the value of the expression a3 + b3 + c3 – 3abc for a = 2, b = 3, c = 4
(a) 3
(b) 6
(c) 9
(d) 27

Hint:
(2)3 + (3)3 + (4)3 – 3(2)(3)(4)
= 8 + 27 + 64 – 72 = 27

Question 32.
If the value of the expression x2 – 5x + k for x = 0 is 5, then the value of k is
(a) 2
(b) 3
(c) 4
(d) 5

Hint:
(0)2 – 5(0) + k = 5
? k = 5

Question 33.
Find the value of the expression 4x – 3 for x = 1
(a) 4
(b) -3
(c) 3
(d) 1

Hint:
4(1) – 3 = 1

Question 34.
Find the value of the expression 100 – 10 x 3 for x = 0
(a) 10
(b) -10
(c) 100
(d) -100

Hint:
100 – 10(0)3 = 100

Question 35.
Find the value of the expression 5n – 3 for n = -1
(a) 5
(b) -3
(c) -8
(d) 8

Hint:
5(-1) -3 = -8

Question 36.
Find the value of the expression x2 + 2x + 1 for x = – 1
(a) 0
(b) 1
(c) -1
(d) 2

Hint:
(-1)2 + 2(-1) + 1 = 0

Question 37.
Find the value of the expression a + b for a = 1, b = 2
(a) 1
(b) 2
(c) 3
(d) 4

Hint:
1 + 2 = 3

Question 38.
Find the value of the expression a2 – 2ab + b2 for a = 1, b = 1
(a) 1
(b) 0
(c) -1
(d) 2

Hint:
(1)2 -2(1)(1) + (1)2 = 0

Question 39.
Find the value of the expression a2 – b2 for a = 2, b = 1
(a) 1
(b) 2
(c) 3
(d) 4

Hint:
(2)2 – (1)2 = 3

Question 40.
Find the value of the expression a2 + b2 for a = 1, b = 0
(a) 1
(b) 0
(c) 2
(d) 4

Hint:
(1)2 + (0)2 = 1

Question 41.
Find the value of the expression a2 + ab + 1 for a = 0, b = 1
(a) 0
(b) 1
(c) -1
(d) 2

Hint:
(o)2 + (o)(1) + 1 = 1

Question 42.
Find the value of the expression 3x + 5 (x – 2) for x = 2
(a) 2
(b) 4
(c) 5
(d) 6

Hint:
3(2)+ 5(2 – 2) = 6

Question 43.
Find the value of the expression z3 – 2(z – 10) for z = 10
(a) 10
(b) 100
(c) 1000
(d) 10000

Hint:
(10)3 – 2(10 – 10) = 1000

Question 44.
What is the coefficient of x in the expression y2x + y?
(a) y2
(b) y
(c) 1
(d) 0

Question 45.
What is the coefficient of x in the expression 2z – 3xz?
(a) 3
(b) z
(c) 3z
(d) -3z